Hypokalaemia and Renal Tubular Acidosis due to Abuse of Nurofen Plus - M. J. Blackstock; A. Lee (Case Reports in Critical Care)
Nurofen Plus is a common analgesic containing ibuprofen and codeine. We present a case of a 38-year-old lady who developed renal tubular acidosis with severe hypokalaemia, after chronic abuse of Nurofen Plus tablets. She presented with confusion and profound biochemical abnormalities requiring critical care admission for electrolyte replacement. Ibuprofen causes renal tubular acidosis due to its effects on carbonic anhydrase activity.